Numerical study on strengthening composite bridges - Narmashiri, K.; Jumaat, Mohd Zamin (2009)
This research examines the effects of using CFRP strips and steel plates for flexural strengthening of composite bridge. Computer simulation is used and adopted from a computer program called ANSYS. The Specimens are modeled in full 3D case, thus the concrete deck, concrete reinforcements, steel profile, steel plates, shear connectors, adhesive and CFRP strips are modeled in 3D solid elements (Tetra 10 node 187). Non-linear static analysis method is used in this research. The steel profile, concrete section and girder length measurements are the same for all models. Polymer strips and steel plate's thicknesses are different for each model, though. The results are compared in stress levels on CFRP strips or steel sheets, strain on adhesive and concrete, and deflection of the bridge girder. The results indicate that stress, strain, deflection, and load bearing in different samples are affected by type of material and thicknesses.